Digital twin embodied interactions design: Synchronized and aligned physical sensation in location-based social VR - Zhang, Ju; Ma, Fang; Pi, Yuke; Du, Haoyang; Pan, Xueni (Frontiers in Virtual Reality, 2025)
Digital twin technologies have become increasingly relevant in virtual reality, offering precise 1:1 mapping between physical environments and their virtual counterparts. While previous work has focused on object interaction through passive haptics, little attention has been given to how such environments can support social and embodied interactions that feel natural and expressive. In this work, we extend the digital twin paradigm by integrating full-body avatars, hand tracking, and voice-driven facial animation into a location-based VR environment. To explore the interactive potential of this dual-realm environment, we propose three categories of cross-realm embodied interaction: (1) Tangible interaction, exemplified by spatially aligned object manipulation; (2) Social gesture, supported through expressive hand and body movement; and (3) Social touch, including co-located tactile actions such as handshakes and hugs. We developed a prototype system showing all three embodied interactions, supported by passive haptics, precise spatial alignment, and real-time multiplayer synchronization. We also introduced a low-cost, Wi-Fi-based motion tracking prototype to enhance interaction with movable physical elements. We evaluate the system through expert interviews, identifying key themes related to spatial trust, tactile realism, and interpersonal presence. Our findings suggested that precise alignment and embodied social cues significantly enhance immersion and social connectedness. This work contributes towards a replicable framework for designing socially immersive digital twin experiences and opens new directions for location-based VR in collaborative and educational contexts.